A comparison of two surgical approaches in functional neurosurgery: individualized versus conventional stereotactic frames. (2nd January 2015) - Matzke, Cornelia; Lindner, Dirk; Schwarz, Johannes; Classen, Joseph; Hammer, Niels; Weise, David; Rumpf, Jost-Julian; Fritzsch, Dominik; Meixensberger, Jürgen; Winkler, Dirk
Abstract: Object : The individualized Starfix® miniframe belongs to a new generation of stereotactic systems enabling high-precision electrode placement with considerably better time-efficiency in deep brain stimulation (DBS). We evaluated the usability and reliability of this novel technique in patients with idiopathic Parkinson's disease (IPD) and compared surgical and clinical results with those obtained in a historical group in which a conventional stereotactic frame was employed. Methods : Sixty patients underwent surgery for implantation of DBS electrodes in the subthalamic nucleus. In 31 of them (group I) a conventional Zamorano-Dujovny frame was used and in 29 of them (group II) a Starfix® miniframe was used. Image fusion of preoperatively acquired 3D T1w and T2w 1.5 T MR-image series was used for the targeting procedure. Placement of the test electrodes and permanent electrodes corresponded to standard functional neurosurgery and included microelectrode recording and macrostimulation. Clinical (L-Dopa equivalent dose, United Parkinson's disease rating scale part III) and time for surgical electrode implantation were evaluated postoperatively in a 3-, 6- and 12-month follow-up. Results : Twelve months postoperatively, L-Dopa dose was significantly reduced from 685.19 to 205.88 mg/day and from 757.92 to 314.42 mg/day in groups I and II, respectively. A comparable reduction of the LED could be observed 1 year after surgery. Motor function has improved in a significant and identical manner with 59% (group I) and 61% (group II). Besides clinical effects by stimulation therapy there was a significantly reduced surgery time required for electrode implantation using the Starfix® miniframe (group I: 234.1 min, group II: 173.6 min; p < 0.001). Conclusions : Individualized miniframes such as the Starfix® miniframe allow implantation of DBS electrodes in IPD that is equally effective as conventional systems. The time efficiency achieved in surgery using of the Starfix® system helps to minimize patients' discomfort during DBS surgery.